Clopidogrel eluting electrospun polyurethane/polyethylene glycol thromboresistant, hemocompatible nanofibrous scaffolds - Shitole, Ajinkya A.; Giram, Prabhanjan S.; Raut, Piyush W.; Rade, Priyanka P.; Khandwekar, Anand P.; Sharma, Neeti; Garnaik, Baijayantimala (Journal of Biomaterials Applications, 2019)
Biomaterials used as blood-contacting material must be hemocompatible and exhibit lower thrombotic potential while maintaining hemostasis and angiogenesis. With the aim of developing thromboresistant, hemocompatible nanofibrous scaffolds, polyurethane/polyethylene glycol scaffolds incorporated with 1, 5, and 10 wt% Clopidogrel were fabricated and evaluated for their physiochemical properties, biocompatibility, hemocompatibility, and antithrombotic potential. The results of physicochemical characterization revealed the fabrication of nanometer-sized scaffolds with smooth surfaces. The incorporation of both polyethylene glycol and Clopidogrel to polyurethane enhanced the hydrophilicity and water uptake potential of polyurethane/polyethylene glycol/Clopidogrel scaffolds. The dynamic mechanical analysis revealed the enhancement in mechanical strength of the polyurethane/polyethylene glycol scaffolds on incorporation of Clopidogrel. The polyurethane/polyethylene glycol/Clopidogrel scaffolds showed a tri-phasic drug release pattern. The results of hemocompatibility assessment demonstrated the excellent blood compatibility of the polyurethane/polyethylene glycol/Clopidogrel scaffolds, with the developed scaffolds exhibiting lower hemolysis, increased albumin and plasma protein adsorption while reduction in fibrinogen adsorption. Further, the platelet adhesion was highly suppressed and significant increase in coagulation period was observed for Clopidogrel incorporated scaffolds. The results of cell adhesion and cell viability substantiate the biocompatibility of the developed nanofibrous scaffolds with the HUVEC cell viability on polyurethane/polyethylene glycol, polyurethane/polyethylene glycol/Clopidogrel-1, 5, and 10% at day 7 found to be 12.35, 13.36, 14.85, and 4.18% higher as compared to polyurethane scaffolds, and the NIH/3T3 cell viability found to be 35.27, 70.82, 36.60, and 7.95% higher as compared to polyurethane scaffolds, respectively. Altogether the results of the study advocate the incorporation of Clopidogrel to the polyurethane/polyethylene glycol blend in order to fabricate scaffolds with appropriate antithrombotic property, hemocompatibility, and cell proliferation capacity and thus, might be successfully used as antithrombotic material for biomedical application.
Keywords: adhesion; cardiovascular; coagulation; electrospinning; Hemocompatible; platelet

Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .